Professional Norms and Race in the North American Video Game Industry - Srauy, Sam (Games and Culture, 2019)
This article examines North American (i.e., Canada and the United States) video game developers’ understanding of race, how they construct narratives when they include characters of different races, and some of the pressures that may shape that process. Discourse analyses of semistructured interview texts found that video game developers operate under an internalized pressure to create game narratives that are quickly understandable and, thus, sellable. This pressure is normatively internalized in the profession as an attempt to hedge against market uncertainty. Video game developers, therefore, depend on social beliefs from the “real world” to inform how video game players might receive their games as well as narratives and themes from past texts such as the works of J. R. R. Tolkien. Therefore, this article argues that racism might be enabled because it is believed to be a hedge against market uncertainty.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé